The Verbal and Non-Verbal Trichotomies in Wolf-Themed Memes: English - Aulia Nur Fadilla Syahputri; Lili Awaludin; R. Myrna Nur Sakinah (Journal of English Development, 2025)
This study investigates wolf-themed memes using Peirce’s semiotic framework to explore how meaning is constructed through verbal and non-verbal elements. The research highlights the importance of understanding these memes in the context of digital culture, where they serve as a medium for emotional expression and commentary. A qualitative content analysis revealed that qualisign and index were the most prominent semiotic elements in wolf-themed memes, emphasizing the role of visual and emotional tones in shaping meaning. The findings demonstrate how textual and visual components work together, with minimalistic choices effectively encapsulating complex themes. By applying a semiotic perspective, this research offers insights into the layered meanings behind wolf-themed memes and their cultural relevance as a form of communication. These results underscore the value of semiotics in interpreting internet memes, revealing their potential as symbolic tools for self-expression and digital interaction.